WordNet Sebagai Basis Pengetahuan Untuk Mengatasi Polisemi Kata-Kata - Sherly Christina (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Information system that accepts data in the form of natural languages often get problemssuch as polysemy in words. Polysemy affects performance of the system to provide accurateinformation. Therefore, it’s needed a knowledge base that can be used to differentiate the meaningof words and find the relationship between words.WordNet is a lexical database that is suggested by several studies to address the polysemy inwords. WordNet contains the set of meanings of words and organized in semantic relations. Thispaper will study some researches that use Wordnet as a knowledge base to solve some ambiguity inpolysemy.